A Methodology to Develop Taxonomy of Additive Manufacturing using Formal Attributes Specification Template - Akmal, S.; Hambali, R.H.; Hashim, S.M.; Maidin, S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Additive Manufacturing (AM) is referring to technology that offers design creativity and freedom in developing the 3D product. AM generates and accumulates a large number of design information on geometrical part, materials, and processes. This is time-consuming for a designer in searching the right information about AM process. In this paper, the additive manufacturing processes have been classified according to their attributes information that is based on a systematic guideline, called Formal Attributes and Specification Template (FAST). FAST is used in the taxonomy generation for formal attribute identification which is later used in Formal Concept Analysis (FCA) to generate a lattice. The resulting lattice and formal attribute information obtained with FCA are later used to create taxonomy. The developed taxonomy was evaluated by homogeneous cluster analysis. The results of the evaluation show that the FAST method provides design rationale in developing AM taxonomy.